THE IRFANI CONCEPT IN SUFISM AND ITS RELATION TO ISLAMIC PHILOSOPHY - Baried, Ariani Barroroh; Hannase, Mulawarman (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
AbstractTalking about Sufism cannot be separated from 'Irfan' knowledge; both are interrelated; it can also say that 'Irfan', and 'Irfan' are Sufism. The level of ma'rifat is a jargon that many Sufis generally pursue. There are many ways to achieve this, each Sufi has his way, including First, Riyadhah (self-surrender, accepting sincerely and gracefully for all that the Creator has), Second, Tafakkur (tafakkur to strengthen belief in the greatness and power of Allah, then become an attitude that always motivates individuals, to actively dhikr and worship Allah swt.), Third, Tazkiyat An-Nafs (the process of purifying the human soul. The process of purification of the soul in the framework of Sufism can be done through the face of takhalli and tahalli). Then when Sufism meets philosophy, can the two synergize with each other? While the science of Sufism talks about the heart while talking about reason or ratio. Because the author wants to release the relationship between Sufism (Irfan) Islamic philosophy, this research is in the form of library research or referred to as library research which is carried out by reviewing various literature, both from the latest journals, book texts, scientific articles, the results of other people's research, as well as other sources related to Irfani Sufism and Islamic philosophy. The results of the conclusion that their studies of the soul in a philosophical approach provided many precious contributions to the perfection of studying Sufism in the Islamic world. An understanding of the soul and spirit itself is essential in Sufism. Later developed philosophical analyses of the soul and spirit in Sufism.